Detection of residues in milk from antibiotics commonly used for treatment of mastitis in selected dairy cattle farms in CALABARZON, Philippines using an optical biosensor - Cerrero, James Allan L. (The Philippine Journal of Veterinary Medicine, 2022)
The study was conducted to detect residues of antibiotics commonly used for the treatment of mastitis using an optical biosensor in milk samples collected from selected dairy cattle farms in CALABARZON (Region IV-A), Philippines. Antibiotic residues could cause health problems and could contribute to antimicrobial resistance. Thus, it is important to detect these residues in milk. Out of 129 samples tested, 43 were used in Anti-microbial Array II and all 129 samples were used in Beta-lactam Array Plus. Antibiotic residues from quinolones, ceftiofur, streptomycin, tylosin, tetracyclines, cephalexin, beta-lactams, and cefuroxime were detected. Among the positive results, three samples had residue levels beyond Maximum Residue Limit (MRL) wherein it was hypothesized that the drinking water of animals was the most probable source of the detected antibiotic residues. Tetracycline, beta-lactams, and a combination of beta-lactams and aminoglycoside drugs were the most used antibiotics. Farm factors such as route of antibiotic administration, dry cow therapy, intrauterine treatment, antibiotic cycling, and the presence of veterinarians in farms have no significant association with the occurrence of antibiotic residues beyond MRL. The results of the study suggest sufficient withdrawal period and proper usage of antibiotics during treatment and that milk, from the selected farms, are safe for consumption.